Inventarisasi Spesies Serangga pada Bunga Clerodendrum paniculatum L. (Lamiaceae) - Nendi Syafrina; - Dahelmi; Siti Salmah (Jurnal Biologi Universitas Andalas, 2014)
A species inventory of insects visited flowering trees of Clerodendrum paniculatum has been conducted at two locations, low land (Bungus Teluk Kabung, Padang, 0-5 m asl.) and high land (Bukittinggi, 813-1013 m asl.). This study used scan sampling and direct collection methods. Insects were identified at the Laboratory of Animal Taxonomy, Biology Department, Faculty of Sciences, Andalas University, Padang. There were totally 28 species of insects that belong to 19 genera, 10 families and three orders that actively visited the flowers. Lepidoptera was the most common insect visited the flower followed by Hymenoptera and Diptera only by one species.Keyword : insects, inventory, flower, Clerodendrum paniculatum.